Formulation of Water Rights Policies as Basic Rights - Wulandari, Andi Sri Rezky; Rahmah, Andi (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2021)
This study aims to analyze the formulation of water rights policies as basic rights. The research method is normative legal research research with legislation and conceptual approaches through the Library Research. The results of this study are in regulating the water resources sector in Indonesia, readiness is needed from all aspects in order to support the need for clean water as the most vital requirement. The legal settings are not only formalistic but also objective. The national policy formulation of water rights starts from ratifying The International Convention on Economic, Social and Cultural Rights (Ekosob) in 2005 through the Republic Indonesia Law Number 11 of 2005 concerning Ratification of International Covenant on Economic, Social and Cultural Rights. The birth of the Republic of Indonesia Law number 11 of 1974, followed by the Indonesian Law Number 7 of 2004 and the Republic of Indonesia Law Number 17 of 2019 had given birth to a shift in water meaning from each law. Likewise with the implementing regulations, namely Government Regulation Number 22 of 1982, Government Regulation Number 42 of 2008, Government Regulation Number 16 of 2005. At the level of the Ministerial, born ESDM Ministerial Regulation Number 31 of 2018, PUPR Ministerial Regulation Number 15 of 2018, PU Ministerial Regulation Number 2 of 2017. At the Regional Government Regulations level, such as Makassar City Government Regulations Number 6 of 2016. At The Village Government Regulation such as in South Sumatera, Born Karang Agung Village Government Regulation Number 7 of 2018.